Analysis of Rotor Lamination Sleeve Loss in High-Speed Permanent Magnet Synchronous Motor - Yiming Tian; Shiqiang Liang; Fukang Wang; Jiahao Tian; Kai Chen; Shi Liu (Machines)
This study addressed the challenges of excessive eddy current losses and elevated thermal risks to permanent magnets in titanium alloy rotor sleeves for high-speed permanent magnet synchronous motors (HSPMSMs). Focusing on a 10 kW, 30,000 rpm high-speed motor, we innovatively propose incorporating insulating layers between axially laminated sleeve structures. Current research primarily mitigates eddy currents through the limited axial segmentation of sleeves/permanent magnets or radial shielding layers, while the technical approach of applying insulating coatings between laminated sleeves remains unexplored. This investigation demonstrated that compared with conventional solid sleeves, segmented sleeves, and carbon fibre sleeves, the laminated structure with a coordinated design of aluminium oxide and epoxy resin insulating layers effectively blocked the eddy current paths to achieve a substantial reduction in the sleeve eddy current density. This research concurrently highlights that the dynamic stress response and long-term operational reliability require further experimental validation. Subsequent investigations could explore optimised lamination patterns, parameter matching of insulating layers, and integration with emerging cooling technologies, thereby advancing synergistic breakthroughs in lightweight design and thermal management for high-speed motor rotors.